Efforts to Improve Gross Motor Skills of 5-6 Year Old Children Through Creative Dance - Seri Rezjeki Wardani Tamba; Ahmad Syukri Sitorus (Prodi Pendidikan Islam Anak Usia Dini Sekolah Tinggi Agama Islam Negeri Mandailing Natal- Sumatera Utara, 2026)
This study was motivated by the low gross motor skills of children aged 5–6 years at RA Istiqomah, particularly in balance, coordination, agility, and movement accuracy. The study aimed to improve children's gross motor skills through creative dance activities. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection stages conducted in two cycles. The participants were 18 children aged 5–6 years in Group B of RA Istiqomah. Data were collected through observation and documentation and analyzed using descriptive qualitative and quantitative techniques. The findings revealed a significant improvement in children's gross motor skills after the implementation of creative dance activities. In the pre-cycle stage, only 22.3% of children reached the categories of Developing as Expected (BSH) and Very Well Developed (BSB). After the first cycle, the percentage increased to 66.6%, and further rose to 94.4% in the second cycle. Children demonstrated improvements in body balance, movement coordination, agility, rhythm synchronization, and muscle strength. In addition, creative dance activities enhanced children's confidence, participation, and enthusiasm during learning activities. The study concludes that creative dance is an effective and engaging learning strategy for improving gross motor skills among children aged 5–6 years. The findings contribute to early childhood education practices by providing an innovative and enjoyable approach to physical motor development. Creative dance can therefore be utilized as an alternative learning activity to optimize children's developmental outcomes.